“CHINESE EXPANSION” IN THE EASTERN REGIONS OF RUSSIA AT THE BEGINNING OF THE XXI CENTURY: THROUGH THE PRISM OF COMPARATIVE ANALYSIS - V. L. Larin (Сравнительная политика, 2020)
Based on the comparative method, the article analyzes the interaction of three subjective and objective realities, which occupy an important place in the contemporary Russian-Chinese relations. Virtual ideas about the scale of the Chinese presence in the Russian Far East are compared with the moods and wishes expressed by Russian authorities and population of this region regarding the involvement of China in the economic development of the region and, after that, are correlated with the realities of the economic and demographic life of the eastern regions of Russia in the second decade of the 21st century. In the first part of the article, the author identifies various sources, modern manifestations and interpretations of the “Chinese threat” phantom, analyzes the views and approaches of the Russian federal center, authorities and the population of Pacific Russia regarding the Chinese economic and demographic presence in the region. The conclusion is drawn about the generally positive attitude of both the authorities and the population regarding this phenomenon. At the same time, there are certain restrictions to close rapprochement with China which exist in the minds of the Russian authorities and the population and affect decisions and actions of local authorities and businesses, as well as a rather cool attitude of the Chinese authorities and big business towards introducing into the economy of this Russian region. The second part of the article is based on offi cial statistics and demonstrates the realities of Chinese participation in the economic life of Pacific Russia: these are the dynamics, scale and structure of interregional trade, the volume and nature of Chinese investment in the Russian Far East, as well as humanitarian exchange and the movement of labor across the border. These statistics convincingly show the very small scale of the Chinese economic presence and influence in the region. A comparative approach allows the author to conclude that there is a deep gap between expert forecasts and unconscious Russian fears about the expansion of «Chinese expansion» in Russia, the intentions of Russian and Chinese politicians to increase the contribution of China to the development of Pacific Russia, and the real extent of this participation.